Sosialisasi dan Edukasi Dampak Pernikahan Dini Terhadap Kehidupan Sosial di Desa Kelincauan Kecamatan Sekatak Kabupaten Bulungan: Pengabdian - Feber, Wempi; Syaini; Maharani Abdul, Kartini; Iskandar; Masruri; Nasroen, Jimmy; Sudirman, Irsyad; Mulyadi, Budi; Rapiandi Isak Merang, K. (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service aims to provide education and knowledge directly related to early marriage which is often found in several areas which are considered normal to avoid promiscuity. The problem of early marriage still often occurs and has not been resolved until now in Kelincauan Village, Sekatak District, Bulungan Regency. The method in this community service activity uses a direct socialization method to the community by providing education to young men and women who are still underage regarding the impact of early marriage on social life in Kelincauan Village, Sekatak District, Bulungan Regency. Furthermore, the results of this community service activity which can provide knowledge and education to underage communities about its direct impact on the social life of the community to avoid unwanted things in the future for the reproductive health of women and men, then daily economic stability and avoid acts of domestic violence that could occur due to the emotional and mental instability of children who marry at an early age.